2021
DOI: 10.1002/npr2.12198
|View full text |Cite
|
Sign up to set email alerts
|

Resolvin D2 attenuates chronic pain–induced depression‐like behavior in mice

Abstract: Aim We previously demonstrated that intracerebroventricular injection of resolvin D2 (RvD2), a bioactive lipid mediator derived from docosahexaenoic acid, ameliorated depression‐like behavior in lipopolysaccharide‐induced and chronic mild stress–induced mouse models of depression. In the present study, we examined the antidepressant effect of RvD2 on chronic pain–induced depression‐like behavior. Methods To prepare the neuropathic pain model, mice were subjected to surgery for unilateral spared nerve injury. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…A long immobility time indicates a high level of depression. The immobility time was reduced after intracerebroventricular (ICV) injection of RvD2 (10 ng) and this antidepressive role of RvD2 was transduced through activation of mTORC1 signalling [ 48 ]. Of interest, the same research group also demonstrated the antidepressant properties of RvD2 (at the same concentration of 10 ng) in two other mouse models of depression induced using endotoxin from Gram-negative bacteria lipopolysaccharide (LPS) or chronic unpredictable stress [ 49 , 50 ].…”
Section: Rvd2/gpr18 Axis In the Resolution Phase Of Inflammationmentioning
confidence: 99%
“…A long immobility time indicates a high level of depression. The immobility time was reduced after intracerebroventricular (ICV) injection of RvD2 (10 ng) and this antidepressive role of RvD2 was transduced through activation of mTORC1 signalling [ 48 ]. Of interest, the same research group also demonstrated the antidepressant properties of RvD2 (at the same concentration of 10 ng) in two other mouse models of depression induced using endotoxin from Gram-negative bacteria lipopolysaccharide (LPS) or chronic unpredictable stress [ 49 , 50 ].…”
Section: Rvd2/gpr18 Axis In the Resolution Phase Of Inflammationmentioning
confidence: 99%
“…In terms of anti-depression, RvD1 plays an anti-depression role through the transmission of glutamic acid or PI3K/AKT signaling, while RvD2 can also act on MEK/ERK [ 127 ]. The activation of mTORC1 signaling is the key anti-depressive role of RvD1, RvD2, RvE1, RvE2, and RvE3 [ 25 , 128 , 129 , 130 , 131 , 132 ]. In addition, RvD2 promotes the healing of periapical bone lesions and the regeneration of pulp-like tissue by enhancing the expression of dentin matrix acidic phosphoprotein 1 (DMP1) and the phosphorylation of STAT3 [ 133 ].…”
Section: Mechanism and Clinical Translation Of Resolvins For Chronic ...mentioning
confidence: 99%